The Stolen Territory: A Cultural Geography of Cape Town's Black Townships - (:unkn) unknown (My University, 1997)
Like other South African cities, Cape Town bears the mark of different ideologies : that of segregation and that of apartheid, legally embodied in urban space as soon as 1901. But the big townships will be developed only from 1948. A detailed study of each Black township brings to light the characteristics of this specifically South African urban model, designed for social and political control of the Blacks. Nevertheless, in landscapes that were forced upon them, Black people managed to develop an original African and urban culture : this is demonstrated by a cultural geography of the townships. Today, the post-apartheid city is appearing, shaped by the inheritances of apartheid, the inertia of space and the formation of new, racially mixed, neighbourhoods.
Keywords: African Research